Development of EGFR TKIs and Options to Manage Resistance of Third-Generation EGFR TKI Osimertinib: Conventional Ways and Immune Checkpoint Inhibitors - Wu, Leilei; Ke, Linping; Zhang, Zhenshan; Yu, Jinming; Meng, Xue (Frontiers in Oncology, 2020)
Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR TKIs) have been first-line therapy in the treatment of non-small cell lung cancer (NSCLC) harboring EGFR sensitive mutations. Progression inevitably happens after 10-14 months of first- or second-generation EGFR TKIs treatment for acquired resistance. Owing to the suc-cessful identification of EGFR T790M, third-generation EGFR TKIs such as osimer-tinib were developed to target such resistance mutation. Nowadays, osimertinib has shown its efficacy both in first-line and second-line after resistance to previous genera-tions of TKIs treatment of EGFR-mutant NSCLC. However, drug resistance also emerges on third-generation EGFR TKIs. Multiple mechanisms of acquired resistance have been identified and some novel strategies were reported to overcome third-generation TKIs resistance. Immune checkpoint inhibitors (ICIs) have dramatically changed the prognosis of selected patients. For patients with EGFR-addicted metastatic NSCLC, ICIs have also revealed a potential role. In this review, we will take stock of mechanisms of acquired resistance to third-generation TKIs and discuss current chal-lenges and future perspectives in clinical practice.